Physicochemical and Sensory Acceptance of Jelly Drink Watermelon Albedo (Citrullus vulgaris) With Soursop Juice (Annona muricata) - Putri Rizky Amalia; Amalya Nurul Khairi (Food ScienTech Journal, 2024)
Red watermelon albedo (Citrullus vulgaris) is a food waste that contains antioxidants, dietary fiber and pectin so it has the potential to be used as a jelly drink. The addition of soursop (Annona muricata) can increase the sour taste, distinctive sweetness, and high vitamin C content. The purpose of this study was to determine the effect of variations in watermelon albedo juice and soursop juice on water content, antioxidant activity, dietary fiber, vitamin C, pH, viscosity and sensory acceptance in jelly drinks. This research method was divided into 3 stages, namely making watermelon albedo juice, soursop juice and jelly drinks. Furthermore, this study was conducted to analyze the physicochemical properties and sensory acceptance of jelly drinks. This study used a completely randomized design (CRD) with variations of watermelon albedo juice and soursop F1 = 100% soursop juice; F2 = 40:60%; F3 = 50:50%; and F4 = 60:40%. The results showed that the jelly drink with a variation of 60:40% had the best antioxidant activity value of 20.97ppm, 3.16% dietary fiber, pH 4.30, viscosity 430.8mPa.s. The more watermelon albedo and soursop juice, The more watermelon albedo added to the jelly drink, the higher the antioxidant activity, dietary fiber, pH, and viscosity, but the lower the water content, vitamin C and sensory acceptance. The best sensory reception results resulted from variations that used more soursop juice.